2015
DOI: 10.1007/s10980-015-0226-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of bird diversity to crop and non-crop heterogeneity in agricultural landscapes

Abstract: Context Habitat heterogeneity is often assumed to benefit farmland biodiversity. Increasing heterogeneity of non-crop habitats is often too costly in terms of agricultural production. It has been suggested that increased crop heterogeneity could mitigate the negative effects of intensification on biodiversity while still maintaining high production levels.Objectives We investigated if habitat-specific species pools of two groups of farmland birds, fieldnesting and non-crop-nesting species, were related to land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 45 publications
8
42
0
2
Order By: Relevance
“…A high diversity of crops with different structure and seasonality is assumed to enable more farmland birds to find both spatially and temporally complementary resources for feeding and nesting within their home range (Vickery and Arlettaz 2012) and hence may compensate for simplified landscape heterogeneity. Accordingly, several studies find that crop diversity enhance bird diversity (Firbank et al 2008, Lindsay et al 2013, Josefsson et al 2017) but there are also examples of studies that have failed to find effects (Fahrig et al 2015, Hiron et al 2015. Our results partly corroborated the positive findings and especially, similar to Josefsson et al (2017), we found that effects was limited to homogeneous landscapes where availability of interstitial seminatural habitats is low.…”
Section: Benefits From Crop Compositionsupporting
confidence: 86%
See 2 more Smart Citations
“…A high diversity of crops with different structure and seasonality is assumed to enable more farmland birds to find both spatially and temporally complementary resources for feeding and nesting within their home range (Vickery and Arlettaz 2012) and hence may compensate for simplified landscape heterogeneity. Accordingly, several studies find that crop diversity enhance bird diversity (Firbank et al 2008, Lindsay et al 2013, Josefsson et al 2017) but there are also examples of studies that have failed to find effects (Fahrig et al 2015, Hiron et al 2015. Our results partly corroborated the positive findings and especially, similar to Josefsson et al (2017), we found that effects was limited to homogeneous landscapes where availability of interstitial seminatural habitats is low.…”
Section: Benefits From Crop Compositionsupporting
confidence: 86%
“…, Hiron et al. ). Our results partly corroborated the positive findings and especially, similar to Josefsson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a lack of detailed information on spatial coverage of measures prevented us from distinguishing between these alternative explanations here. Furthermore, the effects shown here most probably reflect local habitat selection, where higher densities in response to measures are the result of birds aggregating from surrounding poorer habitats (Hiron et al., ). Effects of interventions may also be demographic (with positive effects on juvenile production or overwinter survival).…”
Section: Discussionmentioning
confidence: 88%
“…As response variables, we used farm‐scale species richness and abundance of two trait‐based groups: (a) field‐nesting bird species that nest and forage in fields, and (b) non‐crop nesting bird species that forage both within agricultural fields and non‐crop habitat, but rely largely on non‐crop elements for nesting (see Tables and ; cf. Hiron et al., and Josefsson, Berg, Hiron, Pärt & Eggers, ). For the most commonly occurring species, we also considered individual‐species models.…”
Section: Methodsmentioning
confidence: 95%